1991
DOI: 10.1111/j.1365-2133.1991.tb04954.x
|View full text |Cite
|
Sign up to set email alerts
|

Red tattoo reactions: X-ray microanalysis and patch-test studies

Abstract: Eighteen patients who developed cutaneous reactions to red tattoos were studied to identify the chemicals responsible for the reactions to modern red tattoo pigments. Biopsies from the tattoos were examined histologically and the chemical composition of the red pigments was analysed by X-ray microanalysis. A variety of metallic elements including aluminium, iron, calcium, titanium, silicon, mercury and cadmium were detected. Patch tests were performed to the relevant chemicals in nine cases, and only one patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
92
1
13

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(110 citation statements)
references
References 19 publications
4
92
1
13
Order By: Relevance
“…29 During the period when tattoo inks comprised of inorganic compounds, there lay the risk of toxic and immunologically adverse reactions resulting from the use of these 'heavy'-metal containing pigments. 7 Even though modern organic pigments are claimed to be better tolerated by the skin, the United States Food and Drug Administration (USFDA) has been made aware of more than 150 reports 30 of adverse reactions in consumers tattooed with certain organic pigments. Steinbrecher et al 31 reported a reaction to a specific shade of pigment, but commonly the identity of the causative pigment is not possible to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…29 During the period when tattoo inks comprised of inorganic compounds, there lay the risk of toxic and immunologically adverse reactions resulting from the use of these 'heavy'-metal containing pigments. 7 Even though modern organic pigments are claimed to be better tolerated by the skin, the United States Food and Drug Administration (USFDA) has been made aware of more than 150 reports 30 of adverse reactions in consumers tattooed with certain organic pigments. Steinbrecher et al 31 reported a reaction to a specific shade of pigment, but commonly the identity of the causative pigment is not possible to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that tattoos may cause various systemic and/or cutaneous pathologies. The systemic reactions range from infectious diseases such as hepatitis B or C, AIDS, syphilis, tuberculosis or leprosy to diseases with an immunologic or toxic pathogenic mechanism such as erythema multiforme, toxic shock, urticaria, vasculitis or sarcoidosis 1 . The skin reactions are mainly infectious: warts, herpes simplex, molluscum contagiosum, cellulitis, erysipelas and erysipeloid.…”
Section: Discussionmentioning
confidence: 99%
“…It is observed that white, black, green, blue, and yellow inks rarely cause allergic reactions, while red inks are the most reactive in this regard, due to inclusions of various metals, i.e. aluminium, iron, silicon, titanium, calcium, mercury, cadmium, as well as organic azo colorants (5,(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%